2017
DOI: 10.1108/ijcst-03-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of dye affinity in natural dyeing usingTerminalia chebula retzius(T. chebula) applied to leather

Abstract: Purpose The purpose of this paper is to improve the dye affinity of natural dye of Terminalia chebula retzius (T. chebula) using the dye substrate of leather. Design/methodology/approach The dyeing conditions such as temperature, concentration of dye, and time are controlled by measuring the dye affinity. The effect of enzymatic post-tanning process on dye affinity is evaluated by using different type of proteases such as flavourzyme, alcalase, and bromelain. The optimum conditions for enzymatic post-tanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Few studies have been performed with the aim of evaluating dyeing or fat-liquoring efficiency after using EP in re-bating. Song et al [ 35 ] applied different types of proteases in crust leather dying; study demonstrated better dye absorption in treated leather. Other studies [ 36 , 37 ] with protease in leather dyeing showed high dye exhaustion and better distribution of colour in the finished product.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have been performed with the aim of evaluating dyeing or fat-liquoring efficiency after using EP in re-bating. Song et al [ 35 ] applied different types of proteases in crust leather dying; study demonstrated better dye absorption in treated leather. Other studies [ 36 , 37 ] with protease in leather dyeing showed high dye exhaustion and better distribution of colour in the finished product.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is limited information on ferment usage in post-tanning operations, though these processes are also extremely important for finished leather. Song et al (2017), did research on the protease effect on crust leather dyeing. The study showed better fastness properties against rubbing and better dyes absorption in treated leather.…”
Section: Introductionmentioning
confidence: 99%
“…A post-tanning enzymatic treatment changes the properties of the leather and thus influences the subsequent processes. The study of Song et al [ 26 ] has shown that leather treated with protease flavourzyme showed improved fastness properties against rubbing and dry cleaning compared with untreated leather. The use of enzymes directly in leather dyeing has led to better exhaustion of dye as collagenase-assisted process allows reaching 99% uptake of dye [ 27 ].…”
Section: Introductionmentioning
confidence: 99%